2021
DOI: 10.1155/2021/6652845
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for the Treatment of Severe Interstitial Lung Disease Related to Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease characterized by chronic symmetrical erosive synovitis and extra-articular manifestations, including interstitial lung disease (ILD), whose treatment is nowadays challenging due to high infectious risk and possible pulmonary iatrogenic toxicity. Janus kinase inhibitors, namely, tofacitinib, baricitinib, and upadacitinib, are the latest drug class for the treatment of RA with a good safety profile. We present the case of a patient with RA-ILD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
(32 reference statements)
1
10
0
1
Order By: Relevance
“…Kodera et al [17] described two cases with RA complicated by OP were successfully treated with tofacitinib therapy. Vacchi et al [18] reported successful treatment of severe ILD related to RA with tofacitinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kodera et al [17] described two cases with RA complicated by OP were successfully treated with tofacitinib therapy. Vacchi et al [18] reported successful treatment of severe ILD related to RA with tofacitinib.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies investigated tofacitinib in ILDs. These results collectively indicated that tofacitinib is a potential therapeutic option for RA-UIP [9][10][11][12]. Iguratimod (IGU), a small molecule with new anti-inflammatory and immunomodulatory properties, was developed as a novel anti-rheumatic drug and is widely used for RA.…”
Section: Introductionmentioning
confidence: 94%
“…Rituximab and abatacept has shown promise in ILD, particularly in SSc [ 55 , 56 ]. Recently, tocilizumab has been approved for treatment of SSc-ILD [ 57 •• ]. Refractory IIM-ILD can be treated with calcineurin inhibitors and intravenous immune globulin (IVIG) [ 58 ].…”
Section: Ipaf Managementmentioning
confidence: 99%
“…Among biologic disease-modifying anti-rheumatic drugs (DMARDs) authorized for the treatment of RA, rituximab has shown some promising positive results in published case series of ILD associated to RA or other connective tissue diseases. A 10-year study showed that rituximab may inhibit the development and progression of ILD [ 7 , 8 ]. Also, abatacept in a national multicenter, non-controlled, open-label registry study appeared to be safe in RA-associated ILD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%